Real-life experience with antenatal glucocorticoid administration in premature pregnancies complicated by diabetes mellitus - Anca-Gabriela Dumitrescu; Teodor Salmen; Florentina Furtunescu; Costin Berceanu; Corina Grigoriu; Roxana-Elena Bohîlțea; Simona Daniela Popescu (Clinical and Experimental Obstetrics & Gynecology)
Background: Diabetes mellitus (DM) in pregnancy is associated with an increased risk of premature birth, which therefore increases the risk of acute respiratory distress syndrome (ARDS) of the neonate and is associated with high morbidity and mortality of the newborn. The administration of glucocorticoids to the mother before premature birth decreases the risk of neonatal complications. However, the data regarding the administration of this therapy to mothers with DM is limited. Clinical guidelines recommend treating them in the same manner as the non-DM women, even if there is no recent data to support the benefit in this subpopulation. The aim of this study is to evaluate the real-life effects of glucocorticoid administration on the maternal and fetal prognosis of pregnancies complicated with DM. Material and methods: A retrospective study was conducted on 67 pregnant females who were admitted to the Obstetrics & Gynecology Department of The Emergency University Hospital of Bucharest between December 2016–March 2021, and who received corticosteroid before prematurely giving birth to 70 newborns. There was a group of 33 mothers with DM and a second group with 34 non-DM pregnant women selected for control of glucocorticoids’ real-life administration in the high risk for premature birth population. Results: The administration of glucocorticoids was not restricted by the presence of DM; 78% of the mothers with DM and 79.41% of the mothers without DM received one course of antenatal glucocorticoids for fetal lung maturation (p = 0.6). The incidence of ARDS differs between groups was statistically insignificant: 35.29% in the DM group versus 30.55% in the control group (p = 0.8). There were similar cases of maternal complications such as pregnancy-induced hypertension (PIH), or preeclampsia in the two groups. These findings suggest that glucocorticoid therapy is effective for premature newborns from pregnancies with DM and does not negatively impact the complication rate of the mothers, sustaining their administration in these cases. Conclusions: The administration of antenatal glucocorticoids before premature birth is not influenced by the presence of DM regarding Apgar score at 1 and 5 minutes, the incidence of ARDS, but there were differences such as more large for gestational age (LGA) newborns and neonatal hypoglycemia in the DM group. Considering the low number of patients enrolled from a single-center, future multicentric studies are needed. It is important to emphasize that this study’s findings reflect the local practice and cannot be generalized.